(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Razil the night of the Yahda is one of the most important Iranian celebrations that are at the end of the year. The event, known as Yalda, Chile, Chiang Chile and Shabuneroz, is being held in about 21 or 22 December each year and at the beginning of the winter. The word "ulls" derived from the root of the East-Oil ", which means brightness and light. In the ancient times, this celebration of the sun was linked to the faith and the symbols of the ware and lightning of the land after the dark winter days, known as the mainstream of the Algerian poet in the poorest and some points to cultural and religious occasions and have mentioned in some of his briefs and his songs. Using the language of hair, the maintenance of different maintenance of Iranian culture and is suggested that religious and national concepts are referred to in his poems. It is noted to the beauty of the night and sides of concerts in the poems of beautiful and rich language.